Exploring Students’ Perception of Lecturers’ Teaching Styles in Academic Reading Class - Sumdari Uli Arta Siska; Hardianti Hardianti (Jurnal Lingua Idea, 2025)
This study explores students’ perceptions of lecturers’ teaching styles in the English Education Program at Universitas Esa Unggul. Grounded in Anthony F. Grasha’s (2002) five teaching style framework, like Expert, Formal Authority , Personal Model, Facilitator, and Delegator—the research aims to identify the styles most preferred by students, the reasons behind these preferences, and their perceived impact on learning outcomes. A qualitative descriptive design was employed, supported by a case study approach. Data were collected from 11 participants in the 2023 Academic Reading class through semi-structured interviews and a closed-ended questionnaire based on a Likert scale. Thematic analysis, assisted by Atlas. ti software was used to code and interpret the data. The findings revealed that students most favored a combination of the Expert and Delegator styles. The Expert style was appreciated for lecturers’ mastery of subject matter, clarity of explanations, and corrective feedback, which built students’ trust and confidence in learning. Meanwhile, the Delegator style was valued for fostering autonomy, critical thinking, and collaborative learning, enabling students to take greater responsibility for their own academic progress. Additionally, the Facilitator style was recognized as supportive in encouraging active participation, while the Authority and Demonstrator styles were noted for providing structure and clear guidance. Overall, students emphasized that a balanced approach—combining expertise, structure, and opportunities for independence—leads to more effective and engaging learning experiences. This research contributes to the understanding of how teaching styles influence student motivation, confidence, and engagement in English language learning. It highlights the need for lecturers to adopt flexible, student-centered strategies that integrate both academic rigor and opportunities for autonomy. Future studies are recommended to expand the scope across multiple institutions and incorporate additional methods, such as classroom observations, to strengthen findings.